Assessment of Youth Unemployment Impact on the Socio-Economic Development of Ondo State: A Study of Akure South Local Government Area (American Journal of Social Development and Entrepreneurship, 2023)
Unemployment has become the major source of concern in every society. In recent time, it is often presented as a major problem that is seen to undermine the social-economic development of Nigeria ditto Ondo State. In 2021, the unemployment rate in the country was put at 33% the highest in 13 years. From the figures released by the National Bureau of Statistics (NBS), about 21, 765, 614 Nigerians are jobless within the age group of young people who are between 15-34 years. In comparison to other 181 countries of the world with up-to-date labour data, Nigeria ranks the 41st country with highest unemployment rate. This study assessed the magnitude and dimension of unemployment and its implications on socio-economic development of ondo state referencing unemployed youth in selected communities in Akure South local government area. Several methods were adopted by this study to elicit information; Primary sources of generating data through administration of questionnaires and interviews while secondary sources involve data from journals, articles and internet materials. The study adopted triangulation mixed research methodologies for data collection. Analysis of quantitative data was done using descriptive statistics (sample frequency tables, percentages and numbers.) while qualitative data were analyzed separately. Questionnaires were administered to 350 respondents and 16 interviewees between the ages of 18-35 years through multistage sampling technique. The study relied on Keynesian and Marxist theories as theoretical fulcrum to discuss the multi- dimensional situation of unemployment in Nigeria .The findings from the study revealed that corruption, neglect of Agricultural sector ,infrastructural decay , Bad Leadership and bad governance, unfavourable government reforms and policies, unfavourable terms and conditions for jobs recruitments, ineffective education system, insecurity are among major factors contributing to the rising unemployment in Akure south local government area of Ondo state. The findings also revealed socio-economic implications of youth unemployment to include; poverty, criminalities, insecurity, substance, addiction, psychological effects, health issues, brain drain, dysfunctional social and emotional relationship among others. The study concluded that there are many deleterious socio-economic implications associated with youth unemployment in Akure south local government area of Ondo state.Against this backdrop, the study recommended strong anti-corruption crusades by governments at all levels, infrastructural development, diversification of economic, bail-out funds for ailing industries, enthronement of good leadership and good governance, introduction of Entrepreneurial trainings as part of school academic system and aggressive fight against insecurity as panacea that will checkmate the unemployment scourge.